2015
DOI: 10.1111/hsc.12201
|View full text |Cite
|
Sign up to set email alerts
|

Narrative synthesis of equine-assisted psychotherapy literature: Current knowledge and future research directions

Abstract: Equine-assisted psychotherapy (EAP) is an innovative emerging approach to mental health treatment. This narrative synthesis explores the current state of knowledge and areas for future research in EAP. Specifically reviewed are qualitative and quantitative empirical studies, including both articles published in peer-reviewed journals and research presented in theses and dissertations. We selected 24 studies for final inclusion in this study, dating between 2005 and 2013, and including the first EAP empirical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
(118 reference statements)
0
36
0
Order By: Relevance
“…Equine-facilitated psychotherapy (EFP) is similar to EAP in that a psychotherapist is involved and works with the client towards therapeutic goals; however, mounted activities are also included. (Lee et al, 2016) [7]. …”
Section: Equine-assisted Therapy Farm Animal-assisted Interventiomentioning
confidence: 99%
See 2 more Smart Citations
“…Equine-facilitated psychotherapy (EFP) is similar to EAP in that a psychotherapist is involved and works with the client towards therapeutic goals; however, mounted activities are also included. (Lee et al, 2016) [7]. …”
Section: Equine-assisted Therapy Farm Animal-assisted Interventiomentioning
confidence: 99%
“…A review of equine-assisted therapy by Lee et al (2016) [7] provided a promising analysis of the potential benefits of these kinds of therapies. A case study in Switzerland conducted by Chardonnens (2009) [13] demonstrated that a combination of EAP and EFP improved the behavioral and mental disorders of an eight-year-old boy.…”
Section: Benefits To Children and Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Burgon, EAT is designed to 'provide alternative therapeutic and learning opportunities through experiences with horses alongside specialist practitioners' (Burgon 2011, p. 165). EAT is usually comprised of activities around caring for and handling a horse and can involve aspects of therapeutic riding such as opportunities to sit on and ride the horse with a focus on developing a therapeutic bond (All et al 1999, Lentini & Knox 2009, Lee et al 2016. Given traumatised children can experience a variety of emotional, social, cognitive and behavioural problems, their positive participation and engagement with a therapeutic intervention can be compromised (Waite & Bourke 2013).…”
Section: Equine-assisted Therapymentioning
confidence: 99%
“…, Lentini & Knox , Lee et al . ). Given traumatised children can experience a variety of emotional, social, cognitive and behavioural problems, their positive participation and engagement with a therapeutic intervention can be compromised (Waite & Bourke ).…”
Section: Introductionmentioning
confidence: 97%